Pengaruh Kepemimpinan Transformasional, Sikap Kerja, dan Locus of Control Terhadap Kinerja Guru - Armia, Armia; Rajagukguk, Tumbur Erwin Pandapotan; Adha, Kaharuddin; Panjaitan, Muan Ridani; Silitonga, Eli Irwanto; Lubis, Hasrita; Tarigan, Nur M. Ridha; Nasti, Nilawati; Rahayu, Sri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study has the aim to determine transformational leadership, work attitude and locus of control on teacher performance at SMP Negeri 1 Peureulak, East Aceh Regency. The approach used in this research is a quantitative approach. Data collection is done through library research and questionnaires. The sample in this study amounted to 52 teachers who served in SMP Negeri 1 Peureulak, East Aceh Regency. 1) Transformational leadership has a positive but not significant effect on teacher performance at SMP Negeri 1 Peureulak, East Aceh Regency. The results of this study are evidenced by the value of the coefficient tcount > ttable, which is 0.085 > 1.675 at a significant 0.932 <0.05. This means that the research hypothesis H₀ is rejected and H1 is accepted. 2) Work attitude has a positive and significant effect on teacher performance at SMP Negeri 1 Peureulak, East Aceh Regency. The results of this study are evidenced by the value of the coefficient tcount < ttable, which is 19.468 < 1.675 at a significant value of 0.000 < 0.05. This means that the research hypothesis H₀ is rejected and H1 is accepted. 3) Locus of control has a positive and significant effect on teacher performance at SMP Negeri 1 Peureulak, East Aceh Regency. The results of this study are evidenced by the value of the coefficient tcount < ttable, which is 4.057 > 1.675 at a significant 0.000 > 0.05. It is concluded that the research hypothesis H0 is rejected and H3 is accepted. 4) Transformational leadership, work attitude and locus of control have a simultaneous effect on teacher performance at SMP Negeri 1 Peureulak, East Aceh Regency. The results of this study were proven by the significant value 0.000 <0.05 and the Fcount > Ftable (1026,656 > 3,32). Thus the decision is obtained that H0 is rejected and H4 is accepted. In addition, the multiple linear regression model in this study is feasible to use because it has a positive value. The results of the linear regression test showed a unidirectional effect between the variables X1, X2, X3 on Y. The magnitude of the coefficient of determination (R Square) was R Square 0.984 or equal to 98.4%. This figure means that the variables of transformational leadership, work attitude, locus of control simultaneously (together) affect the teacher's performance variable by 98.4%. While the remaining 1.6% which is the result of 100% - 98.4% = 1.6% is influenced by other variables.